Impact of Bioactive Ingredients on the Fecal Excretion of Aflatoxin B1 and Ochratoxin A in Wistar Rats - Pilar Vila-Donat; Dora Sánchez; Lara Manyes; Alessandra Cimbalo (Molecules)
This study evaluates the effects of fermented whey (FW) and pumpkin (P) on the excretion of aflatoxin B1 (AFB1) and ochratoxin A (OTA) in rats using immunoaffinity column cleanup and high-performance liquid chromatography–fluorescence detection (IAC-LC-FLD). The method achieved detection limits of 0.1 µg/kg for AFB1 and 0.3 µg/kg for OTA, with recovery rates ranging from 72–92% for AFB1 and 88–98% for OTA. A fecal analysis of 100 rats showed peak AFB1 concentrations of 418 µg/kg and OTA of 1729 µg/kg. In the toxin-exposed groups, OTA levels were higher than AFB1, with males in the OTA-only group showing significantly higher OTA (1729 ± 712 µg/kg) than females (933 ± 512 µg/kg). In the AFB1-only group, the fecal levels were 52 ± 61 µg/kg in males and 91 ± 77 µg/kg in females. The AFB1 + FW group showed notable AFB1 concentrations (211 ± 51 µg/kg in males, 230 ± 36 µg/kg in females). The FW + P combination further influenced excretion, with higher AFB1 and OTA levels. These findings suggest that FW and P modulate mycotoxin excretion and may play a role in mycotoxin detoxification, providing insight into dietary strategies to reduce mycotoxin exposure and its harmful effects.